Competing with the grey market: Puzey and Payne in Zimbabwe. Issue 2 (5th March 2018) - Simba, Amon; Smith, David J.; Dube, Tatenda
Abstract : Synopsis: The case study analyses competition in the automobile industry in Zimbabwe, a developing economy. From that perspective, it discusses Puzey and Payne's business operations; a company with a long-standing history in the country's automobile industry. Since its establishment during the Colonial era, the company endured a prolonged period of rapid car and spare parts sales decline in 2012. Following a management buyout deal in 2013, the decline in sales proved to be its real dilemma and it required strategic decisions to diffuse the impact of the "grey markets". Government policies added to the company's problems. Research methodology: The case study follows a qualitative research approach. Information about Puzey and Payne's business operations was gathered from archived materials, through qualitative conversations as well as company artefacts. Published materials in newspapers and magazines were used to provide background information. Relevant courses and levels: The case study is appropriate for both undergraduate and postgraduate students studying International Business Management.